Morphosis : A responsive membrane - Diniz, N.; Branco, C.; Dias, J.; Turner, A. (Computer-aided architectural design futures (CAADFutures) 2007: Proceedings of the 12th International CAAD Futures Conference, 2007)
In this paper, we introduce Morphosis: A Responsive Membrane, which physically responds to movement, light and sound interacting spatially and temporally with the environment and their inhabitants. The fundamental hypothesis is to create architectural systems as living, evolving materials. The dynamic of the material is produced by dozens of actuators made by Shape Memory Alloys (SMAs) and LED’s which react in real time to change the behavior of the membrane. The system is controlled by a genetic algorithm in an attempt to develop a technological approach to performance skins that possess adaptive and evolutionary personality relative to changing phenomena of the environment of buildings.